HELICOBACTER PYLORI PREVALENCE AND HISTOPATHOLOGICAL FINDINGS IN DYSPEPTIC PATIENTS - Mehmood, Khalid; Awan, Abdul Aleem; Muhammad, Naveed; Hasan, Fariha; Nadir, Abdul (Journal of Ayub Medical College Abbottabad, 2014)
Background: Helicobacter pylori (H. pylori) colonizes in half of the population of developed and nearly all inhabitants of developing countries. The infection is characterized by gastritis but can present more complicated disease states. We intended to report prevalence of H. pylori infection by histopathology and presence of gastritis, activity, atrophy and intestinal metaplasia in dyspeptic patients of Islamabad, Pakistan. Methods: Ninety four patients identified to be dyspeptic on the basis of Rome-III criteria were included in the study and diagnosed for H. pylori status by Histopathology. The grading and severity of gastritis was documented as nil, mild, moderate or severe, based on the Sydney system. Activity was recorded as present when an increase in the number of neutrophils was observed. Atrophic changes and intestinal metaplasia were also determined. Results: Eighty three out of total 94 (88.3%) patients were positive for H. pylori on histopathology. Out of total 94 patients, chronic gastritis was observed in 89 (94.6%), evidence of activity was found in 37 (39.4%), atrophic changes were observed in 66 (70%) and intestinal metaplasia was present in 4 (4.3%) patients. Conclusion: H. pylori infection in dyspeptic patients of Islamabad appears to be more related with gastritis. Keywords: Helicobacter pylori, Histopathology, Dyspepsia, Gastritis, Pakistan